Kapabilitas Ekonomi Sirkular dalam Sektor UMKM Kota Surakarta Menuju Smart-Sustainable City - Muhammad Alfarizi; Ngatindriatun Ngatindriatun (Badan Riset dan Inovasi Daerah Kota Surakarta, 2024)
The increase in waste correlates with changes in consumption habits and population expansion. The Circular Economy, a primary focus in addressing climate change, promotes recycling and material integration in production. Industry 4.0 plays a crucial role with technologies like IoT, big data, and AI, enhancing raw material efficiency and waste reduction. SMEs in Surakarta have significant potential in transitioning towards a sustainable economy, leveraging their creativity to innovate in sustainable practices. This study aims to analyze the capabilities of SMEs in Surakarta in circular economy practices towards achieving a sustainable-smart city. Employing a quantitative approach, the study surveyed 215 research respondents using convenience sampling. Data analyzed through Partial Least Square-Structural Equation Modeling (PLS-SEM) highlights the pivotal role of Industry 4.0 readiness in adopting IIoT and big data analysis, driving circular economy practices. Managerial recommendations for SMEs include enhancing technological readiness and adopting the